Charonne : « Un événement déraisonnable qui a ses raisons » - Jacques Revel (L'Atelier du CRH)
Charonne : “An Unreasonable Event That Has Its Own Reasons”On February 8, 1962, Paris was the place of a state massacre. Around the metro station Charonne, 9 persons died from police violence. The occasion was a demonstration against ultra-right terrorism during the last weeks of the Algerian War. Published in 2006, Dewerpe’s close study of the episode makes clear that it was a true “State affair”. Beyond such an abstraction, beyond the now trivialized notion of “State violence”, a meticulous examination of their practices makes it possible to endow them with concrete contents and to trace the reasons behind the actions of the different protagonists which were confronted during the short time of the event: the forms of collective mobilization, the chain of political and administrative command and responsabilities, the police culture and practices, the legal and judicial processing of the case, the memory that follows it over time. Charonne raises therefore a number of questions on the legitimate limits of public action and on what a democracy could mean in France during the second half of the 20th century.